Developmental patterns of change in the influence of safe and risky peer choices on risky decision‐making. Issue 1 (14th August 2018) - Braams, Barbara R.; Davidow, Juliet Y.; Somerville, Leah H.
Abstract: Adolescents take more risks when peers monitor their behavior. However, it is largely unknown how different types of peer influence affect adolescent decision‐making. In this study, we investigate how information about previous choices of peers differentially influences decision‐making in adolescence and young adulthood. Participants ( N = 99, age range 12–22) completed an economic choice task in which choice options were systematically varied on levels of risk and ambiguity. On each trial, participants selected between a safer choice (low variability in outcome) and a riskier choice (high variability in outcome). Participants made choices in three conditions: a solo condition in which they made choices with no additional information, a social condition in which they saw choices of supposed peers, and a computer condition in which they saw choices of a computer. Results showed that participants' choices conform to the choices made by the peers, but not a computer. Furthermore, when peers chose the safe option, late adolescents were especially likely to make a safe choice. Conversely, when the peer made a risky choice, late adolescents were least likely to follow choices made by the peer. We did not find evidence for differential influence of social information on decisions depending on their level of risk and ambiguity. These results show that information about previous decisions of peers are a powerful modifier for behavior and that the effect of peers on adolescents' decisions is less ubiquitous and more specific than previously assumed. Abstract : We investigated developmental changes in the impact of peers' choices on risky and ambiguous choices. Results show that social information is a more powerful modifier than computer generated information. Furthermore, adolescents were most influenced by safe decisions of others, and this age group was least influenced by risky decisions of others. Here, we show that the effect of peer on adolescents' decisions is less ubiquitous and more specific than previously assumed.